2021
DOI: 10.1038/s41598-021-84301-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training and burdock root (Arctium lappa L.) extract independently improve abdominal obesity and sex hormones in elderly women with metabolic syndrome

Abstract: The prevalence of metabolic syndrome (MS) is increasing among the elderly, and new lifestyle-based treatment strategies are warranted. We conducted a randomized, double-blind controlled trial of the effects of aquatic exercise (AE) and/or consumption of burdock root extract (BE) on body composition and serum sex hormones, i.e., testosterone, estradiol, sex hormone-binding globulin (SHBG), and dehydroepiandrosterone-sulfate (DHEA-S) in elderly women with MS. The percentage of abdominal fat was decreased in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The burdock extract was prepared according to a method previously described by our research group [ 20 , 21 , 25 ]. In brief, after harvest in the Sangcheong region (Gyeongnam, Korea), the burdock root was washed and dried, subsequently heated at 100 °C for 3 h, and extracted at 0.7 kg/cm 2 pressure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The burdock extract was prepared according to a method previously described by our research group [ 20 , 21 , 25 ]. In brief, after harvest in the Sangcheong region (Gyeongnam, Korea), the burdock root was washed and dried, subsequently heated at 100 °C for 3 h, and extracted at 0.7 kg/cm 2 pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise is well-known as an effective treatment for MS and CVD [ 18 ]. Notably, aqua exercise is an ideal form of exercise for overweight and older women, as it is a systemic exercise in which the buoyancy of water decreases the body weight by 90%, thus minimizing the risk of injury [ 19 , 20 , 21 ]. In previous studies on older women, aqua exercise was shown to effectively improve blood pressure, insulin resistance, and CVD risk factors [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized, double-blind, controlled study was assessed to evaluate the effects of aquatic exercise and A. lappa root extract consumption on abdominal obesity and sex hormones in elderly women with metabolic syndrome. The combined effect of aquatic exercise and A. lappa root extract consumption exerted no synergistic and/or additive effects on any sex-related outcome measures in women with metabolic syndrome [21]. Clinical studies of A. lappa and its products against different ailments are shown in Fig.…”
Section: Clinical Studiesmentioning
confidence: 96%
“…Randomized clinical studies have also been conducted to evaluate the potential of burdock against certain diseases such as influenza [16], viral pneumonia [17], Covid-19 [18], Acne vulgaris [19], knee osteoarthritis [20], and abdominal obesity [21]. Moreover, A. lappa L. has had a significant impact in the field of nanotechnology, contributing to antimicrobial, anticancer and anti-diabetic nanomedicine.…”
Section: Introductionmentioning
confidence: 99%